The influence of principal's academic supervision and work motivation on teacher performance at public elementary schools in Tembilahan Hulu district, Indragiri Hilir regency - Kaswito Teguh; Sumarno; Putri Yuanita (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The research objectives are (a) to determine the influence of the principal's academic supervision on teacher performance, (b) to determine the influence of work motivation on teacher performance, and (c) to determine the influence of the principal's academic supervision and work motivation on teacher performance at the Tembilahan Hulu District State Elementary School. The type of research carried out is survey research with a quantitative research approach. The population and sample are elementary school teachers in Tembilahan Hulu District, Indragiri Hilir Regency. The research population was 289 teachers, and the research sample was 156 teachers taken randomly. The data collection technique was a questionnaire measured using a Likert scale. The data analysis technique used in this research is quantitative descriptive analysis. Based on the study and discussion described above, the conclusion is that school principal supervision significantly influences teacher performance. Furthermore, there is a significant influence between work motivation and teacher performance at the Tembilahan Hulu District State Elementary School. Then we get an R Square value of 0.574 or 57.4%, meaning that the influence of the principal's academic supervision and teacher work motivation (X2) on teacher performance (Y) is 57.4%, while the rest is determined by other factors that are not part of from this research.